PENERAPAN STANDAR AKUNTANSI ENTITAS MIKRO KECIL DAN MENENGAH PADA CATERING GHANI - Bambang Setyobudi Irianto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Small and medium enterprises are a potential economic forces. However, many small and medium enterprises have not kept accounting records properly. The purpose of this community service is to provide insight and examples of the application of accounting standards to small and medium enterprises. The results of the community service show that small and medium enterprises need assistance in applying accounting standards.